Diversity and Conflict. Issue 2 (20th March 2020) - Arbatlı, Cemal Eren; Ashraf, Quamrul H.; Galor, Oded; Klemp, Marc
Abstract : This research advances the hypothesis and establishes empirically that interpersonal population diversity, rather than fractionalization or polarization across ethnic groups, has been pivotal to the emergence, prevalence, recurrence, and severity of intrasocietal conflicts. Exploiting an exogenous source of variations in population diversity across nations and ethnic groups, as determined predominantly during the exodus of humans from Africa tens of thousands of years ago, the study demonstrates that population diversity, and its impact on the degree of diversity within ethnic groups, has contributed significantly to the risk and intensity of historical and contemporary civil conflicts. The findings arguably reflect the contribution of population diversity to the non‐cohesiveness of society, as reflected partly in the prevalence of mistrust, the divergence in preferences for public goods and redistributive policies, and the degree of fractionalization and polarization across ethnic, linguistic, and religious groups.